Why God’s Justice Is Good News God’s Generosity, Impartiality, and Equity in Romans - Prothro, James B. 1986- (2025)
God’s "justice" (δικαιοσύνη) is a key theme in the Letter to the Romans, associated with divine judgment of sin and with God’s salvation of sinners. These two aspects of divine justice are difficult to synthesize, and scholarship tends toward narrow definitions of "justice" either as necessarily strictly retributive (and thus as antithetical to Paul’s gospel) or as a faithful beneficence (and thus not retributive). Drawing on other research, I find both interpretations unsatisfactory. Reviewing "justice" in non-Jewish and Jewish discourse, my argument shows a broader conception of justice as including retribution but resisting its strict application for the common good, paired also with generosity, equity, and impartiality. Thereafter, I revisit the argument of Romans to show how the dimensions of such justice underlie Paul’s presentation of the gospel, illuminating God’s patient and impartial judgment of sin, God’s ordering of judgment toward salvation in history, and Paul’s participatory soteriology of life for sinners who die with Christ.
Keywords: Pauline Theology; Romans; Justice; Justification; righteousness of God